Looming Over the Nation, Uneasy with the Folks: Locating Mike de Leon in Philippine Cinema - Campos, Patrick F. (Humanities Diliman: A Philippine Journal of Humanities, 2007)
The article draws on filmic, popular, and scholarly references in order to trace how Mike de Leon and his films have been regarded, since his landmark entrance into Philippine cinema as director, up to the present. Specifically, it locates De Leon within the subtly shifting discourse of nationalist film scholarship and historicizing, and discusses how he and his films are written about, identified, associated or networked with other filmmakers and films, or utilized in discourses about the Philippines, Philippine cinema, or Philippine culture. The article locates De Leon as (1) an insider of Philippine cinema history, (2) an outsider of the commercial film industry, and (3) a hero of the mythic Golden Age of the National Cinema. It also maps out his filmography within the nationalist agenda; appraises what filmmakers, commentators, and scholars have articulated about his films; and analyzes the thematic and stylistic trajectories of his later works. Finally, it discusses how De Leon is being written into today’s discourse of Philippine cinema.
Keywords: Mike de Leon, film criticism, film history, nationalism, institutional dynamics/myths